Alih Kode Dalam Program Acara Hitam Putih Episode 10 Juni 2019 - Dewi Kartika (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the types of code-switching, code-switching functions, and the factors that cause code-switching in the Hitam Putih program episode 10 June 2019. The method used in this study is qualitative descriptive. The data source for this research is the Hitam Putih episode 10 June 2019. The data collection method uses the listening method which has basic and advanced techniques. The data collection instrument used a data card. The validity of the data is done by using triangulation. The data analysis techniques in this study used the equivalent method. Te results of this study are based on the analysis there are types of code-switching, namely internal code-switching and external code-switching. Internal code switching includes switching from Indonesian to Javanese and Javanese to Indonesian, while external code-switching includes switching Indonesian to English, English to Indonesian, and English to Javanese. In addition, there is a code-switching function which includes respecting the interlocutor, asking something, building intimacy with the interlocutor, ordering, creating a sense of humor, and explaining something as well as the factors that cause code-switching incluiding the speaker, the interlocutor, the prensence of a third person, and the topic of conversation. Keywords: Code-Switching, Code-Switching Function, Factors Causing Code-Switching